2002
DOI: 10.1089/088922202753519142
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1-Specific IgE in Serum of Long-Term Surviving Children Inhibits HIV Type 1 Productionin Vitro

Abstract: We previously identified a group of long-term pediatric survivors who had acquired HIV-1 through maternal transmission; had not received antiretroviral therapy; are now >8 years old, in good health, and with no opportunistic infections; and have not failed to thrive, although they have greatly decreased numbers of blood CD4+ T cells (<500/mm(3)). All the children have elevated total serum IgE levels (210-2475 IU/ml) and make anti-HIV-1 IgE or IgE directed against non-HIV-1 specificities (radioimmunoassay, West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…Similar studies in our laboratory [3] in HIV-1 disease have revealed a persistence of HIV-1-specific IgE after 210 days, and retained its ability to suppress HIV-1 production in vitro [3]. Further, we have demonstrated that specific IgE anti-HIV-1 antibodies may protect against HIV-1 disease progression by promoting cytotoxic responses or by suppressing virus production [2][3][4]. Thus, the association of IgE with viral infection and immunity could be consistent with an important immune function of IgE.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar studies in our laboratory [3] in HIV-1 disease have revealed a persistence of HIV-1-specific IgE after 210 days, and retained its ability to suppress HIV-1 production in vitro [3]. Further, we have demonstrated that specific IgE anti-HIV-1 antibodies may protect against HIV-1 disease progression by promoting cytotoxic responses or by suppressing virus production [2][3][4]. Thus, the association of IgE with viral infection and immunity could be consistent with an important immune function of IgE.…”
Section: Discussionsupporting
confidence: 87%
“…The fact that this study demonstrates the presence and persistence of IgE anti-parvovirus B19 antibodies as late as 3 years after presentation of symptoms and in both healthy and immunodeficient patients elucidates a unique characteristic of IgE biology. Similar studies in our laboratory [3] in HIV-1 disease have revealed a persistence of HIV-1-specific IgE after 210 days, and retained its ability to suppress HIV-1 production in vitro [3]. Further, we have demonstrated that specific IgE anti-HIV-1 antibodies may protect against HIV-1 disease progression by promoting cytotoxic responses or by suppressing virus production [2][3][4].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In fact, in previously conducted researches, the authors noted that IgE has antiviral action, acting effectively. 55 Similarly, in two of his studies, Karagiannis et al showed that IgE antibodies are able to increase the survival of animals bearing ovarian carcinoma through the ADCC mechanism against tumor cells. 56,57 In our study, we did not assess the specificity of IgE antibodies, and thus, it is not possible to associate the production of this antibody to protection mechanisms against tumor cells in the patients studied.…”
mentioning
confidence: 93%
“…Previous studies in our laboratory demonstrated that IgE may play an important role in immunity to specific viruses including Parvovirus B19 [30], Varicella Zoster Virus [31,32], Influenza Virus [33] and HIV-1 [34,35] In addition, earlier studies in our laboratory found that serum from certain HIV-1 infected pediatric long-term survivors contain agents that inhibit HIV-1 production in vitro, including anti-HIV-1 IgE [34]; it has been suggested that cytotoxicity plays a role in anti-HIV-1 IgE-mediated inhibition of virus production [35] Thus, these specific IgE responses may play an important role in viral memory responses, and provide protection against viral infection.…”
Section: Discussionmentioning
confidence: 99%